Efficient cryogenic cooling during machining of rolled AISI 4340 steel - Ahmed, Mirghani Ishak; Hrairi, Meftah (Trans Tech Publications, Switzerland, 2012)
Cryogenic cooling is an environmental friendly and effective cooling technology. The present work investigates the role of cryogenic cooling on tool wear at various cutting conditions. An indigenous method of applying cryogenic coolant was developed. Different methods of circulating the liquid nitrogen and vaporizing it inside the tool holder were tried with the objective of lowering down the temperature at the cutting zone. This was achieved through more efficient heat transfer. As-rolled AISI 4340 steel shafts were turned using coated cemented carbide inserts. Results of tool wear show improvement of tool life during cryo-machining as compared to dry machining especially when heavy depths of cut, high feed values and high cutting speeds are employed. The effect of cryogenic cooling was not pronounced at low speeds, small feed and depths of cut.